Penerapan Kode Etik Jurnalistik Di Media Cetak Harian DI’S Way - Risma Nuur Aliyya (DIGICOM : Jurnal Komunikasi dan Media, 2023)
The daily DI''s Way is one of the traditional newspaper-based journalism products published in 2020 amid the COVID-19 pandemic, even at a time when many newspaper publishers in any country are starting to raise their hands. This research discusses the application of the jurnlistic code of ethics to the reporting and writing of news in the Daily DI'sway. In the research entitled the application of the journalistic code of ethics to reporting and writing news in the Daily DI's Way, it uses qualitative research methods. In its application, the qualitative approach uses data collection methods and analysis methods through in-depth interviews. From the results of observations made and interviews with daily journalists in the Di's way, the application of the Code of Journalistic Ethics they always try to follow the provisions of the Code of Journalistic Ethics when reporting, especially in collecting and presenting news or information. The results of the study found that the di's way daily journalists' knowledge of the Code of Journalistic Ethics was relatively good. The implementation of the Journalistic Code of Ethics for Journalists in Di's Way also strives to comply with all the rules in the Code of Journalistic Ethics. Especially in the rules of the Code of Journalistic Ethics in pursuing professional ways of reporting in the field. Di's Way also continues to try to create new ways of covering news and dealing with sources who find it difficult to provide information that will be used as news material, so that they can get the information they need.